MAQASHID AL-SHARIAH IN EDUCATION FOR ENHANCING THE QUALITY OF TEACHERS AND EDUCATIONAL PERSONNEL - Muhammad Misbakul Munir Misbah; Harapandi Dahri (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2026)
This study examines the implementation of Maqāṣid al-Sharīʿah in enhancing the quality of teachers and educational personnel at Muhammadiyah Boarding School (MBS) Ki Bagus Hadikusumo Bogor. Using a qualitative case study design, data were collected through in-depth interviews, observations, and document analysis, and analyzed thematically based on a systems-oriented maqāṣid framework. The findings reveal that the institutional philosophy of al-uṣūl al-khamsah—comprising sound faith, proper worship, noble character, comprehensive knowledge, and social contribution—functions as an operational translation of maqāṣid principles in educational practice. These values are systematically integrated into recruitment, professional development, performance evaluation, and daily institutional culture. Teachers and educational personnel are developed not only as competent professionals but also as individuals with strong ethical integrity, spiritual awareness, and social responsibility. The study also finds that organizational practices such as continuous training, collective leadership, and value-based discipline reinforce a holistic model of human resource development. This research demonstrates that Maqāṣid al-Sharīʿah provides a relevant and adaptable framework for improving educational quality by integrating intellectual, moral, and institutional dimensions. The findings contribute to the development of a value-based educational model and offer practical insights for strengthening human resource management in Islamic educational institutions. Keywords: Islamic Educational Institutions, Maqashid Shariah, Teachers and Educational personnel  Abstrak Penelitian ini mengkaji implementasi Maqāṣid al-Sharīʿah dalam meningkatkan kualitas guru dan tenaga kependidikan di Muhammadiyah Boarding School (MBS) Ki Bagus Hadikusumo Bogor. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus, di mana data dikumpulkan melalui wawancara mendalam, observasi, dan analisis dokumen, kemudian dianalisis secara tematik berdasarkan kerangka maqāṣid berbasis sistem. Hasil penelitian menunjukkan bahwa filosofi institusi al-uṣūl al-khamsah—yang meliputi akidah yang lurus, ibadah yang benar, akhlak mulia, ilmu yang komprehensif, dan kontribusi sosial—berfungsi sebagai bentuk operasionalisasi prinsip maqāṣid dalam praktik pendidikan. Nilai-nilai tersebut terintegrasi secara sistematis dalam proses rekrutmen, pengembangan profesional, evaluasi kinerja, serta budaya kelembagaan sehari-hari. Guru dan tenaga kependidikan tidak hanya dikembangkan sebagai profesional yang kompeten, tetapi juga sebagai individu yang memiliki integritas etis, kesadaran spiritual, dan tanggung jawab sosial yang kuat. Penelitian ini juga menemukan bahwa praktik kelembagaan seperti pelatihan berkelanjutan, kepemimpinan kolektif, dan disiplin berbasis nilai memperkuat model pengembangan sumber daya manusia yang holistik. Maqāṣid al-Sharīʿah terbukti memberikan kerangka yang relevan dan adaptif dalam meningkatkan kualitas pendidikan melalui integrasi dimensi intelektual, moral, dan kelembagaan, serta berkontribusi pada pengembangan model pendidikan berbasis nilai dan penguatan manajemen sumber daya manusia dalam lembaga pendidikan Islam. Kata Kunci: Guru dan Tenaga Kependidikan, Lembaga Pendidikan Islam, Maqashid Shariah